2016
DOI: 10.3389/fphar.2016.00241
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Pharmacogenomics into the Clinical Setting: Training Future Pharmacists

Abstract: Pharmacogenomics, once hailed as a futuristic approach to pharmacotherapy, has transitioned to clinical implementation. Although logistic and economic limitations to clinical pharmacogenomics are being superseded by external measures such as preemptive genotyping, implementation by clinicians has met resistance, partly due to a lack of education. Pharmacists, with extensive training in pharmacology and pharmacotherapy and accessibility to patients, are ideally suited to champion clinical pharmacogenomics. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…There have been advances in PGx implementation, but significant barriers remain, including those preventing clinical implementation . The remaining hurdles include improving physician and pharmacist awareness and education about PGx, the development of tools to implement PGx results into the workflow of physicians and pharmacists, and the undecided reimbursement of PGx tests. Finally, and most importantly, evidence presenting the collective clinical utility of a panel of PGx‐markers remains to be established.…”
Section: Pharmacogenomics In Precision Medicinementioning
confidence: 99%
“…There have been advances in PGx implementation, but significant barriers remain, including those preventing clinical implementation . The remaining hurdles include improving physician and pharmacist awareness and education about PGx, the development of tools to implement PGx results into the workflow of physicians and pharmacists, and the undecided reimbursement of PGx tests. Finally, and most importantly, evidence presenting the collective clinical utility of a panel of PGx‐markers remains to be established.…”
Section: Pharmacogenomics In Precision Medicinementioning
confidence: 99%
“…Previous studies have shown that incorporating active learning experiences in PG would increase student interests [ 54 ]. Additional innovative learning methods in PG have been recently adopted, such as Pharmacogenomics Education Program 3 (PharmGenEd™) open online courses [ 9 ] and personal genotyping [ 52 , 55 , 56 ]. When teaching PG through practical applications, students learn to use genetic information in the framework of medication management, allowing them to understand the significance of PG applications in clinical practice [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers and facilitators of implementation of pharmacogenetics into health care have been widely studied (Deverka et al, 2007;Swen et al, 2007;Haga and Burke, 2008;Altman et al, 2011;Ieiri, 2012;Bell et al, 2014;Perry et al, 2016;Frick et al, 2016;Hicks et al, 2016;Abbasi, 2016;Kapoor et al, 2016). Main hurdles that are described include the need for improvement in physician and pharmacist awareness and education about PGx, more insight in relevant measures for clinical validity and utility of (preemptive) PGx testing (Tonk et al, 2017;Jansen et al, 2017), and a proper infrastructure to integrate pharmacogenetics into the workflow of physicians and pharmacists (van der Wouden et al, 2017;Slob et al, 2018).…”
Section: Introductionmentioning
confidence: 99%